Study of Small Molecule Organic Solar Cells Performance Based on Boron Subphthalocyanine Chloride and C60. (12th November 2013) - Ke, Jhong-Ciao; Wang, Yeong-Her; Chen, Kan-Lin; Huang, Pao-Hsun; Huang, Chien-Jung
Abstract : The small molecule organic solar cells based on boron subphthalocyanine chloride (SubPc) and C60 by varying the SubPc layer thickness from 3 nm to 21 nm were fabricated. The maximum power conversion efficiency (PCE) of 1.47% was obtained at the 9 nm SubPc layer under 100 mW/cm 2 AM1.5G illumination, which is attributed to reach the optimal balance between the light absorption efficiency and the carrier collection efficiency in the device. To increase the open-circuit voltage (V oc ) of device, the molybdenum oxide (MoO3 ) and poly(3, 4-ethylenedioxythiophene):poly(styrene sulfonate) were inserted between the indium tin oxide and the SubPc layer, respectively. Finally, the V oc of device increased from 0.46 V to 1 V by using MoO3 buffer layer, resulting in the fact that the PCE of device increased from 1.47% to 2.52%.